Histopathology of Polyps and Cancer of Colorectum: A ten years study from a tertiary care center - Goyal, Binita (Journal of Gandaki Medical College-Nepal, 2021)
Introduction and objectives: Polyps and colorectal cancer have overlapping clinical presentation and may be difficult to diagnose on clinical grounds alone and close clinicopathological correlation is required for correct diagnosis and management. This study was aimed to see the spectrum of polyps and cancer in colorectum, see the percentage of colorectal cancer in younger individuals, see association between histologic grade and pathologic stage at presentation and compare site of tumor and pathologic stage at presentation in younger and older age group. Methods: This study was carried out on 138 consecutive cases of polyps and malignant lesions of colorectum during a time period of 10 years from January 2011 to December 2020. Results: Age of the patients ranged from 2 – 90 years with mean 45.1 years and a male female ratio 2:1. There were 58 (42.0%) cases of polyps and 80 (58.0%) cases of malignancies. 37 (46.3%) malignancy cases were seen in individuals ≤ 50 years of age. Most common site of involvement was rectum in 80 (58.0%) cases. Most common non-neoplastic polyp was retention polyp comprising 25 (67.6%) and most common neoplastic polyp was adenoma comprising of 18 (85.7%) cases. Most common malignancy was adenocarcinoma comprising 75 (93.8%) cases. Conclusion: Significant number of malignancies is seen in younger individuals stressing the need for suspicion and surveillance in this age group. Histologic grade is an important prognostic parameter and there is no difference in site of tumor and stage at presentation between younger and older age group.